The effect of cooperatives credit to the welfare - Inayati Nuraini Dwiputri; Lustina Fajar Prastiwi; Grisvia Agustin; Mochammad Daffa Ibrahim (UTMS Journal of Economics, 2022)
Cooperatives are considered to have provided benefits and advantages for the community who are members of the cooperative especially, both households, community groups and business actors. However, with the development of the world economy, the existence of cooperatives is now considered to be starting to shift. One of the assumptions in society that is currently arising is that cooperatives have started to lose the principles of kinship, especially savings and loan cooperatives which have started to be profit-oriented, so the impact of these cooperatives is starting to be questioned. Therefore, this study wants to identify the effect of savings and loan cooperatives in improving people's welfare and increasing the performance of businesses. Regression analysis shows that the use of credit savings and loan cooperatives can have a positive effect in improving people's welfare. This research can be used as the basis for formulating community policies in an effort to improve community welfare through cooperatives.
Keywords: F63; F61; G18; G21; 330; saving; loan; cooperative; welfare; omzet